2008
DOI: 10.1139/o08-032
|View full text |Cite
|
Sign up to set email alerts
|

The role of expansion segment of human ribosomal protein L35 in nuclear entry, translation activity, and endoplasmic reticulum docking

Abstract: The phylogenic alignment of homologous L35 protein suggests that human large subunit ribosomal protein L35 carries a 54 aa eukaryotic expansion segment (ES) at the C-terminal end. Within this ES, the first 25 amino acid residues were found to be essential for the nuclear import of the protein. The last 29 residues of the ES were shown to be uninvolved in the ribosome's structural and translational functions, although this region proved to be one of the contact sites for ribosomal docking to endoplasmic reticul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…However, it could be demonstrated that human L35 r-protein binds to nucle(ol)ar pre-60S r-particles in HeLa cells (44). Consistently, it has also been shown in HeLa cells that L35 is imported to the nucleus due to the presence of a NLS within the C-terminal part of the protein (108). In this study, we present several lines of evidence that yeast L35 assembly occurs in the nucle(ol)us.…”
Section: Discussionsupporting
confidence: 55%
“…However, it could be demonstrated that human L35 r-protein binds to nucle(ol)ar pre-60S r-particles in HeLa cells (44). Consistently, it has also been shown in HeLa cells that L35 is imported to the nucleus due to the presence of a NLS within the C-terminal part of the protein (108). In this study, we present several lines of evidence that yeast L35 assembly occurs in the nucle(ol)us.…”
Section: Discussionsupporting
confidence: 55%
“…This complexity suggests that many molecules that were not initially imported were added later to the import repertoire in a piecemeal fashion by acquiring a diversity of NLS recognized preferentially by different karyopherins. Some ribosomal proteins show clear evidence of the later addition of NLS in expansion segments [276], an example of the quantum evolutionary impact on ribosomes of the origin of the nuclear envelope earlier postulated [3,70]. Though one might think that replication and repair enzymes and RNA polymerases were among the early molecules imported [3], it remains unclear how many of these, especially RNA polymerase are imported [277]; the case of transcription initiation factors is interesting in emphasizing that in a large macromolecular complex only some (minimally one) constituents needs an NLS - thus TAF10 a component of transcription factor complex TFII (that recognizes TATA boxes) and other transcription regulatory complexes lacks an NLS but is imported by being bound to three proteins with histone fold domains that contain NLS [278]; these histone-fold factors might themselves have evolved from core histones and thus ancestrally would have had NLSs.…”
Section: Results: the Origin Of Mitosis And The Nucleusmentioning
confidence: 99%
“…Recently information on the structure of eukaryotic ribosome has greatly progressed [10], and the characteristics of the expansion segments (ES) of ribosomal rRNA and ribosomal peptides in eukaryotic ribosome have been gradually revealed [10], [11], [12], [13], [14]. These studies have suggested that the ES is often exposed on the surface of ribosome particle [10], [11], [12], [13], [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…These studies have suggested that the ES is often exposed on the surface of ribosome particle [10], [11], [12], [13], [14], [15]. Thus, the potential surface property of an ES might provide a useful means of generating a surface-specific antibody against eukaryotic ribosome particles.…”
Section: Introductionmentioning
confidence: 99%